Correlation analysis of agronomic characteristic in F2 population in rice (Otyza sativa) / Mohd Faridhul Atrash Ahmad Ramly - Ahmad Ramly, Mohd Faridhul Atrash (Faculty of Applied Sciences, 2014)
Rice is a common staple food for all Malaysian consumers, but with the population of 26 million and annual growth rate of 2.5%, there is a need to increase the rice grain production to ensure food security through the promotion of rice selfsufficiency. However there is some problem in producing the good quality of rice especially for F2 population. This study performed to determine the association between agronomic characteristics components in sixty-three selected rice genotypes at F2 populations. Results on correlation coefficient analysis showed that there are strong positive correlations between filled grains per panicle with total grain number (r = 0.768) followed by correlation between filled grains per panicle with 1000-grain weight (r = 0.678). Path coefficient analysis revealed that filled grains per panicles were directly associated with total grain number and 1000-grain weight. The greatest indirect effect belonged to grain length, plant height and number of tillers. Information obtained in this study revealed that traits, filled grains per panicle, total grain number, 1000-grain weight, panicle length and flag leaf length could be used as selection criteria for grain yield improvement at segregating populations of rice.